Brown adipose tissue activity in hypocaloric-diet fed lactating rats. Issue 7 (July 1986) - Villarroya, Francesc; Felipe, Antonio; Mampel, Teresa
Abstract : Hypocaloric diet feeding reduced the mitochondrial protein content and whole tissue GDP-binding in interscapular brown adipose tissue from both virgin and lactating rats. A reduction in brown fat lipoprotein lipase activity was also detected in underfed virgin and lactating animals. These results indicate that lactation in the rat, even though it produces a reduction in brown fat activity, does not impair the capacity of the tissue to respond to a diminished caloric intake by lowering its activity further.